2017
DOI: 10.5455/jice.20170721062527
|View full text |Cite
|
Sign up to set email alerts
|

Ethnopharmacological survey of medicinal plants with hallucinogenic effect and plants used against pain, inflammatory diseases, diabetes and urinary lithiasis in Zagora “Morocco”.

Abstract: Aim:The aim of this study was to identify different plants used in folk medicine for treating pain, inflammatory diseases, diabetes and kidney stones by the population of Zagora province, in Southeastern of Morocco. This investigation was undertaken during more than 2 years started in 2013 and ended in 2015. Materials and Methods: A total of 1400 person with different ages between 20 and 80 years, in 12 areas, was included in this survey; 348 were diabetics, 292 were suffering from kidney stones and 760 health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 30 publications
1
5
1
Order By: Relevance
“…We also note that the higher the concentration, the high the percentage of increase of glucose uptake by the yeast cells, which amounted to 73.03% at a concentration of 0.5g/mL. These results support the ethnopharmacological use of the B. muricata as an anti-diabetic plant (Boufous et al, 2017). It is not hidden from us that there are many plants belonging to the Chenopodiaceae family that have an anti-diabetic property, mentioned in the use of traditional medicine and confirmed by scientific research as Haloxylon scoparium, Atriplex halimus, and Anabasis articulata (Chikhi et al, 2014;Kambouche et al, 2009;Lachkar et al, 2021).…”
Section: Glucose Uptakesupporting
confidence: 78%
See 1 more Smart Citation
“…We also note that the higher the concentration, the high the percentage of increase of glucose uptake by the yeast cells, which amounted to 73.03% at a concentration of 0.5g/mL. These results support the ethnopharmacological use of the B. muricata as an anti-diabetic plant (Boufous et al, 2017). It is not hidden from us that there are many plants belonging to the Chenopodiaceae family that have an anti-diabetic property, mentioned in the use of traditional medicine and confirmed by scientific research as Haloxylon scoparium, Atriplex halimus, and Anabasis articulata (Chikhi et al, 2014;Kambouche et al, 2009;Lachkar et al, 2021).…”
Section: Glucose Uptakesupporting
confidence: 78%
“…In Algeria it is used for diarrhea and skin diseases, specifically to treat dermatosis, pustules, boils, and infected wounds (Hammiche & Maiza, 2006). In Morocco, it is an antidiabetic (Boufous et al, 2017). In Saudi Arabia, seed oil is used in the treatment of sores (Awad, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Only 13 of the interviewed had a higher level. These results are not similar with those reported by Boufous et al, 30 The predominance of Lamiaceae in Morocco and its high biodiversity has been reported in several studies 31,32 . Moreover, Lamiaceae and Asteraceae family's were also the most reported in Moroccan ethno-pharmacological studies 33,34 .…”
Section: Fig 4: Parts Of Plants Used Fig 5: Mode Of Preparation Of contrasting
confidence: 78%
“…Other ethnomedicinal studies reported that T. satureioides was also used as an antispasmodic and antinociceptive agent, and for the treatment of bronchitis, skin ailments, circulatory disorders, urogenital problems, nervous and visual ailments, and menstruation pains [ 1 , 5 , 11 , 12 , 33 ].…”
Section: Resultsmentioning
confidence: 99%